Conditioned by Race: How Race and Religion Intersect to Affect Candidate Evaluations. Issue 3 (1st April 2016) - McLaughlin, Bryan; Thompson, Bailey A.
Abstract: While it is becoming increasingly clear that religious cues influence voter evaluations in the United States, work examining religious cues has largely overlooked the conditioning role of race. We employed a 2 × 2 (White candidate vs. Black candidate) × (racial cues vs. no racial cues) online experiment with a national sample ( N = 397; 56% white, 46% black) where participants were exposed to a fictitious congressional candidate's webpage. Results show that White participants expected the religious candidate to be more conservative, regardless of race, while Black participants did not perceive a difference in ideology between the religious and non-religious Black candidates. Additionally, when it comes to candidate favorability, religious cues matter more to White participants, while racial cues are most important to Black participants. These findings provide evidence that religious and racial cues activate different assumptions among White and Black citizens.